A new fluorescent and colorimetric chemosensor for Al3+ and F−/CN− based on a julolidine unit and its bioimaging in living cells. Issue 54 (4th September 2018) - Liu, Fangfang; Fan, Congbin; Tu, Yayi; Pu, Shouzhi
Abstract : A novel multifunctional chemosensorHL bearing a julolidine unit and a Schiff base unit has been synthesized. Abstract : A novel multifunctional chemosensorHL bearing a julolidine unit and a Schiff base unit has been synthesized. As a fluorescent sensor, HL exhibited excellent selectivity and high sensitivity to Al 3+ and F − /CN − with a low detection limit in acetonitrile. Moreover, HL also showed good colorimetric selectivity to F − /CN − ; a solution color change from colorless to light yellow in acetonitrile was observed by the 'naked-eye'. The properties ofHL with Al 3+ and F − /CN − were studied by UV-vis absorption spectroscopy, fluorescence spectroscopy, high-resolution mass spectrometry and 1 H NMR titration. Furthermore, the cell imaging experimental results indicated that the chemosensorHL could be applied for the detection of Al 3+ in living cells.